2011
DOI: 10.1242/jeb.057935
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity develops with maturation in the deep-diving hooded seal

Abstract: SUMMARYMaturation in hooded seals is characterized by the rapid development of their physiological diving capacity and is accompanied by increases in oxidant production but not oxidative damage. To test the hypothesis that the antioxidant system of hooded seals develops as they transition from a terrestrial to an aquatic environment, we obtained the complete cDNA sequence that encodes the NF-E2-related factor 2 (Nrf2), a central regulator of the antioxidant response, and compared Nrf2 mRNA and protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
4
21
1
Order By: Relevance
“…Elephant seal pups also increase their antioxidant defenses at the end of their postweaning fast, suggesting that the activation of the antioxidant system in these mammals is an essential part of their developmental process and prepares them to dive, which is the next step in their life history (Vázquez-Medina et al, 2010;Vázquez-Medina et al, 2011c) suggest that, because apnea stimulates the adaptive response to oxidative stress, and the number and duration of apneas increase with development in elephant seal pups, apnea is essential to prime the seal's antioxidant mechanisms that allow them to cope with the subsequent diving-induced hypoxemia and ischemia/reperfusion/ reoxygenation while at sea. Maturation-related increases in antioxidant capacity have also been documented in the deep-diving hooded seal (Vázquez-Medina et al, 2011a;Vázquez-Medina et al, 2011b), in which oxygen stores (hemoglobin and Mb content), acid buffering capacity, and aerobic and anaerobic enzyme activities also increase with maturation in the skeletal muscle (Burns et al, 2007;Burns et al, 2010;Lestyk et al, 2009). In the present study, repetitive apneas increased Mb expression and HIF-1 nuclear content in the skeletal muscle of elephant seals.…”
Section: Eupneasupporting
confidence: 74%
See 1 more Smart Citation
“…Elephant seal pups also increase their antioxidant defenses at the end of their postweaning fast, suggesting that the activation of the antioxidant system in these mammals is an essential part of their developmental process and prepares them to dive, which is the next step in their life history (Vázquez-Medina et al, 2010;Vázquez-Medina et al, 2011c) suggest that, because apnea stimulates the adaptive response to oxidative stress, and the number and duration of apneas increase with development in elephant seal pups, apnea is essential to prime the seal's antioxidant mechanisms that allow them to cope with the subsequent diving-induced hypoxemia and ischemia/reperfusion/ reoxygenation while at sea. Maturation-related increases in antioxidant capacity have also been documented in the deep-diving hooded seal (Vázquez-Medina et al, 2011a;Vázquez-Medina et al, 2011b), in which oxygen stores (hemoglobin and Mb content), acid buffering capacity, and aerobic and anaerobic enzyme activities also increase with maturation in the skeletal muscle (Burns et al, 2007;Burns et al, 2010;Lestyk et al, 2009). In the present study, repetitive apneas increased Mb expression and HIF-1 nuclear content in the skeletal muscle of elephant seals.…”
Section: Eupneasupporting
confidence: 74%
“…Plasma, tissues and RBCs of seals possess higher basal activities of several antioxidant enzymes and higher glutathione (GSH) levels than those of terrestrial mammals (Murphy and Hochachka, 1981 . Furthermore, hypoxia-inducible factor 1 (HIF-1), a key transcriptional regulator of the adaptive response to hypoxia, and NF-E2-related factor 2 (Nrf2), which controls the adaptive response to oxidative stress by upregulating antioxidant genes in response to increased oxidant production, have also been implicated in seal's protection against apnea-induced hypoxemia and ischemia/reperfusion (Johnson et al, 2004;Johnson et al, 2005;Vázquez-Medina et al, 2011b). No in vivo studies, however, have been conducted to elucidate the cellular and molecular responses that protect seals against apnea-induced hypoxemia and ischemia/reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular adjustments during apnea in seals result in ischemia to peripheral tissues, which can induce tissue hypoxia (Ponganis et al, 2006;Ponganis et al, 2008;Stockard et al, 2007). The increase in the number and duration of sleep apneas is associated with an increase in antioxidants (Vázquez-Medina et al, 2010;Vázquez-Medina et al, 2011b) over the course of the post-weaning fast. Furthermore, it was recently demonstrated that plasma XO activity, HX and xanthine content increase in elephant seal pups in response to rest-and voluntary submersion-associated apneas (Vázquez-Medina et al, 2011c).…”
Section: Purine Metabolism Increases With Fastingmentioning
confidence: 99%
“…Increases in intracellular oxidant generation modify Cys273 and Cys288 residues in Keap1, inhibiting Nrf2 ubiquitination and promoting its nuclear translocation and binding to the EpRE (Bloom and Jaiswal, 2003;Kobayashi et al, 2004;Kobayashi et al, 2006;Zhang and Hannink, 2003). The Nrf2 of the seal has high identity to the Nrf2 of other mammals, contains the conserved leucine zipper domain, key residues for nuclear export signal and Keap1-mediated degradation, and is expressed at the mRNA and protein level in seal muscle (Vázquez-Medina et al, 2011a;Vázquez-Medina et al, 2011c). Moreover, nuclear accumulation of Nrf2 increases in the skeletal muscle of the elephant seal in response to repetitive bouts of apnea-induced ischemia/reperfusion (Vázquez-Medina et al, 2011c), which are frequent at the end of the post-weaning fast (Thorson and Le Boeuf, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Fasting activates Nrf2 in seals muscle (Vázquez-Medina et al, 2011a;Vázquez-Medina et al, 2011c). Moreover, nuclear accumulation of Nrf2 increases in the skeletal muscle of the elephant seal in response to repetitive bouts of apnea-induced ischemia/reperfusion (Vázquez-Medina et al, 2011c), which are frequent at the end of the post-weaning fast (Thorson and Le Boeuf, 1994).…”
mentioning
confidence: 99%